Development of a generic model-assisted control algorithm for building HVAC systems. (September 2017) - Baranski, Marc; Fütterer, Johannes; Müller, Dirk
Abstract: Universally applicable building automation and control systems could contribute largely to reducing both the environmental impact and the operation costs of buildings. We present a building HVAC control algorithm that excites small subsystems and uses the system responses to calibrate prefabricated Modelica models. It uses these models for distributed model-assisted online control. We demonstrate and evaluate the algorithm in simulations and real-life experiments on a central air handling unit. Results show that the algorithm is capable of controlling the systems. Its performance is comparable to the reference scenario based on PI controllers.